Avaliação da efetividade da escovação supervisionada com dentifrício fluoretado na promoção de saúde bucal em escolares residentes em comunidades ribeirinhas do Estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Pará, 2014)
The objective of this study was to evaluate the effectiveness of a program to promote oral health on caries control of adolescents in riverine communities in the Amazonas State. This is a prospective longitudinal experimental study, whose interventions were allocated for population groups (schools) and the outcome was measured at the individual level. The test interventions were based: education for oral health and daily tooth brushing with fluoride toothpaste, supervised by teachers on a school routine. The control intervention included oral health education and periodic distribution of toothbrushes and fluoride toothpaste. The schools were divided into test and control groups, and the data were collected before (baseline) and six months after the beginning of the interventions. There were included students in the age group of 15 to 19 years enrolled in state schools in the city of Careiro da Várzea / AM. For outcome evaluation, the clinical variables collected were: Nyvad criteria for caries activity evaluation, bleeding index and plaque index; being complemented by a socioeconomic questionnaire. Clinical examination and data collection were performed by a previously calibrated dentist [Kappa Coefficient for Nyvad criteria: k = 0.72 (95% CI: 0.69 to 0.76)]. The associations between the outcome (caries activity) and clinical and socioeconomic variables were tested in multivariate logistic regression, estimating the brute and adjusted odds ratio. After six months of interventions, 51.7% of the non-cavitated active lesions in the test group and 37.8% of these lesions in the control group became inactive or health surfaces. Individuals in the control group had 1.93 (95% CI: 1.07 to 3.49) more chance to have no improvement in caries activity than the individuals in the test group (p=0.0289). Demonstrating that daily supervised brushing with fluoride toothpaste (test intervention) was more effective than the simple distribution of toothbrushes and fluoride toothpaste (control intervention) in the caries control.
Keywords: Saúde bucal - Comunidades ribeirinhas - Amazonas; Cárie dentária - Comunidades ribeirinhas - Amazonas; Escovação dentária - Comunidades ribeirinhas - Amazonas; Dentifrícios; Oral health; Dental caries; Toothbrushing; Fluoride toothpaste; CIÊNCIAS DA SAÚDE